Musical Expression of the Malagasy in Contemporary Christian Churches in Madagascar: Between Tradition and Inculturation - Muszkalska, Bożena (Interdisciplinary Studies in Musicology, 2025)
The article discusses the process of formation and transformation of musical expression in Christian communities in Madagascar from the first attempts at evangelization in the 16th century to the present day. This phenomenon is presented in a broad historical and cultural context, taking into account the role of music as a tool for evangelization, a medium for sustaining cultural identity, and a space for religious and artistic syncretism. The evolution of Catholic and Protestant missionary strategies, the origins of the zafindraony genre, the significance of traditional hira gasy performances, and the impact of liturgical reforms initiated after the Second Vatican Council are discussed. It is emphasized that Christian music in Madagascar is a dynamic synthesis of elements of local and European culture, serving as an example of inculturation and adaptation of Christianity to the realities of postcolonial society.